Populasi Buaya Senyulong (Tomistoma schlegelii) di Taman Nasional Tanjung Puting Kabupaten Kotawaringan Barat Kalimantan Tengah - Sosilawaty; Mohamad Rizal; Johansyah; Reynol Sainz Situmeang (Journal of Environment and Management, 2020)
Indonesia known as center of Senyulong Crocodile (Tomistoma schlegelii) habitat in Southeast Asia, beside Sarawak and Peninsula Malaysia, Thailand and Brunei Darussalam. In the country, the crocodile can be found in East Sumatra, Kalimantan, and West Java. This research aims to determine the population and structure of Senyulong Crocodile (Tomistoma schlegelii) in Tanjung Puting National Park in West Kotawaringin District, Central Kalimantan. As the results, as many as 56 individuals of Senyulong Crocodile were found in the Camp Leakey Area (Sekonyer Kanan River) to Muara (Muara Ali) within the park, including 8 adult individuals, 15 individual children, and 33 individual infants. Opportunities for the appearance of one individual in the census (p) are 0,58 with a standard deviation (S) of 3.90. Population density (N) estimated about 16.09 individuals. The average observed individual from each observation (x?) was 9.33 individuals.